Perancangan Alat Bantu Hand Stacker Dengan Kapasitas 500 Kg di PT. Titian Kencana Samudera Jaya - Gampang Gedhe Sasongko; Rizal Indrawan; Fipka Bisono; Sharon Diaz Rahayu (Proceedings Conference On Design Manufacture Engineering And Its Application, 2023)
PT Titian Kencana Samudera Jaya is one of the companies engaged in Engineering, Fabrication and Construction. The hand stacker itself can be used to lift, lower, and move materials from one place to another. This type of lifting mechanism on the hand stacker uses a pulley system. Hand stacker with a size that fits the dimensions of the company makes it easier to move materials and several machines to be worked on. In this design, product development uses the Ulrich method. The concept selection in this design uses a pulley system as a lifting system where compared to the hydraulic system, the pulley system has a longer displacement distance because the pulley system uses a 6 x 19 IWRC steel rope and lifts goods faster because it uses a motor drive. The results of this research found that this tool saves more time to lift and use a motor that greatly facilitates workers and avoids excessive fatigue. This tool is made from UNP canal, and hollow which has dimensions of 1100mm long x 600 mm wide x 1750 mm high. The cost of designing this tool is Rp. 6,197,400, -